Normal Rate of Speech in Kannada - Venkatesh CS; Purushothama G; Poornima MS (Journal of All India Institute of Speech and Hearing, 1970)
Traditionally 'Rate of Speech' is defind as the number of words spoken per minute during a speech performance. That would include all pauses — intentional and unintentional and meaningful words spoken in unit elapsed time. In this  study,  the  number of syllables  per minute were onsidered instead of words.